PENGUJIAN KARAKTERISTIK PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Idamiharti Idamiharti; Venny Darlis (Jurnal Pembangunan Nagari, 2017)
The purpose of this study was to examine the influence of size, profitability (ROE), leverage (DER), growth and the firm environment performance (proper) on Corporate Social Responsibility Disclosure (CSRD) in Indonesia. This research employed food and beverage companies that listed in Indonesia Stock Exchange (ISE) in the period 2009-2013 as its samples. Using multiple linear regressions, the results show that leverage (DER) and growth were not significantly influence CSRD yet, firms’ size, profitability (ROE) and the firm environment performance (proper) have significant effect on CSRD.